Diode Laser Absorption Spectroscopy of Lithium Isotopes - Olivares-Bahamondes, I (Springer Verlag, 2016)
We study Doppler-limited laser intensity absorption, in a thermal lithium vapor containing 7Li and 6Li atoms in a 9 to 1 ratio, using a narrow-linewidth single-longitudinal-mode tunable external cavity diode laser at the wavelength of 670.8 nm. The lithium vapor was embedded in helium or argon buffer gas. The spectral lineshapes were rigorously predicted for D1 and D2 for the lithium 6 and 7 isotope lines using reduced optical Bloch equations, specifically derived, from a density matrix analysis. Here, a detailed comparison is provided of the predicted lineshapes with the measured 7Li-D2, 7Li-D1, 6Li-D2 and 6Li-D1 lines, in the case of high vapor density and with intensity above the saturation intensity. To our knowledge, this is the first time that such detailed comparison is reported in the open literature. The calculations were also extended to saturated absorption spectra and compared to measured Doppler-free 7Li-D2 and 6Li-D2 hyperfine lines. © 2016, Springer-Verlag Berlin Heidelberg.